1994
DOI: 10.1139/v94-135
|View full text |Cite
|
Sign up to set email alerts
|

Partial molar volumes of some drugs in water and ethanol at 35 °C

Abstract: Partial molar volumes, vO, of six drugs, mostly anaesthetics, viz., cinchocaine HCl, lidocaine HC1, mepivacaine HC1, procaine HC1, propranolol HC1, tetracaine HCI, in water and ethanol, calculated from precision densities obtained at 35OC from a vibrating tube densitometer, are reported in this work. The data represent the smaller volumes of drug molecules in ethanol than in water. Volume contribution of hydrochloride part were calculated and excluded from V O to assess the volume of free base component of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 14 publications
(18 reference statements)
4
11
0
Order By: Relevance
“…The   v is intrinsic volume plus volumetric effects due to solute-solvent interactions such as ion-solvent interactions, H-bonding etc. The partial molar volume of drug-HCl is due to individual ionic contributions of   v Drug and   v HCl (Marcus, 2006;Iqbal et al, 1994;Delgado et al, 2010) significant change in the φ 0 v of drug is observed from pure water to aqueous-DMSO mixtures and pure DMSO. The φ 0 v value of drug in all the systems is positive due to existence of strong drugsolvent interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The   v is intrinsic volume plus volumetric effects due to solute-solvent interactions such as ion-solvent interactions, H-bonding etc. The partial molar volume of drug-HCl is due to individual ionic contributions of   v Drug and   v HCl (Marcus, 2006;Iqbal et al, 1994;Delgado et al, 2010) significant change in the φ 0 v of drug is observed from pure water to aqueous-DMSO mixtures and pure DMSO. The φ 0 v value of drug in all the systems is positive due to existence of strong drugsolvent interactions.…”
Section: Resultsmentioning
confidence: 99%
“…been studied. Apparent molar volume and adiabatic compressibility of aqueous solutions of some drugs and partial molar volumes of some drugs in water and ethanol were studied (Iqbal and Verrall, 1989;Iqbal et al, 1994). Physicochemical properties of some drugs in solution (Baluja et al, 2007) have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the first quantity was obtained from the molecular structure according to the method of Van Krevelen, the molar volume was calculated from an additive-constitutive group contribution method. , Remember that, for substances which are solid at room temperature, the molar volume of the solute to consider in estimating their solubility or partition coefficient is not that of the crystalline substance, but the volume of the molecule in its hypothetical supercooled liquid state. However, to account for a certain amount of volume contraction due to the strong H-bonded complexes that some molecular groups may form with water, the obtained volumes of the molecules containing these particular groups were systematically decreased by 15% in the aqueous phase as was previously done for the water solubility predictions. , …”
Section: Resultsmentioning
confidence: 99%
“…Actually, the presence of the solute molar volume in the log P thermodynamic predictive equation naturally arises from the volume dependence of both the mobile order and mixing entropy. PAH log P pred ) -1.152 + 0.0333V B (19) PCB log P pred ) -0.843 + 0.0333V B (20) aliphatic esters log P pred ) -2.431 + 0.0333V B (21) aliphatic ketones log P pred ) -2.487 + 0.0333V B (22) aliph primary alcohols log P pred ) -2.082 + 0.0333V B (23) aliph tertiary amines log P pred ) -2.468 + 0.0279V B (24) steroids (1 ester + 1 s OH) log P pred ) -4.462 + 0.0279V B (25) …”
Section: Resultsmentioning
confidence: 99%
“…21,22 However, as for the aqueous solubility predictions, the obtained volumes were, in the case of the steroids and of any molecule containing an aliphatic amine, systematically decreased by 15% in the water phase. Such reduction accounts for the volume contraction [23][24][25][26] of these molecules consecutively to the H-bonded complexes they form with the water molecules. Taking the aforementioned remarks into account, the n-octanol-water partition coefficient of selected substances, including compounds of environmental, medicinal, and pharmaceutical relevance, is estimated using the standard stability contants reported in Table 1.…”
Section: The Molecular Origin Of the Partition Coefficientmentioning
confidence: 99%